Territorial Development in the Amazon of Paraense: impacts on the lifestyle of the São José Community (Research, Society and Development, 2022)
This article is integral part of a master's research entitled "Ways of life in the São José Community: Conflicts, Territories and Territorialities in the face of the Implementation of the Albras/Alunorte Project (Barcarena-Pará)", presented to the Interdisciplinary Graduate Program in Cities , Territories and Identities (PPGCITI), from the Federal University of Pará (UFPA), Abaetetuba. The article aims to present the possible relationships about the discourse of development, developmentalism and its reverberation in the São José Community, in dialogue with the different fronts of transformations that took place in Barcarena, of a material and immaterial order: economic, territorial, industrial, structural, housing, cultural heritage, and their respective impacts on the ways of life of the residents above mentioned community. This is a research with a qualitative approach, historiographical type anchored in Oral History through the technique of semi-structured interviews carried out with 5 (five) residents of the investigated community. It is based on the writings of Duarte, Sarmento, Ponte, Maia, Silva et al. The results indicate that the construction and execution of development projects that sought to integrate and optimize the exploration of the Amazon space promoted territorial changes with the arrival/operation of new business ventures arising from the mining and metallurgical industrial activity and the entire infrastructure network bringing profound changes, implications and material transformations in the living conditions of families from the São José community, as a consequence, provoked a dynamic field of deterritorialization and the constitution of the identity of this population.